2022
DOI: 10.1111/ele.14101
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal plasticity driven by variation in fitness across species and environmental gradients

Abstract: Dispersal plasticity, when organisms adjust their dispersal decisions depending on their environment, can play a major role in ecological and evolutionary dynamics, but how it relates to fitness remains scarcely explored. Theory predicts that high dispersal plasticity should evolve when environmental gradients have a strong impact on fitness. Using microcosms, we tested in five species of the genus Tetrahymena whether dispersal plasticity relates to differences in fitness sensitivity along three environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 90 publications
(151 reference statements)
2
20
0
Order By: Relevance
“…On a final note, interdisciplinary studies are also a promising approach to examine (evolutionary changes in) dispersal plasticity under different environmental conditions (Campana et al, 2022).…”
Section: Integrative Approaches Addressing Emerging Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On a final note, interdisciplinary studies are also a promising approach to examine (evolutionary changes in) dispersal plasticity under different environmental conditions (Campana et al, 2022).…”
Section: Integrative Approaches Addressing Emerging Questionsmentioning
confidence: 99%
“…On a final note, interdisciplinary studies are also a promising approach to examine (evolutionary changes in) dispersal plasticity under different environmental conditions (Campana et al, 2022). Meta‐population experiments have recently shown that dispersal plasticity is impacted by top‐down and bottom‐up effects (Cote et al, 2022; Fronhofer et al, 2018) including potential consequences for meta‐foodweb stability.…”
Section: Further Advancing the Field: Linking Theory Experimental Evo...mentioning
confidence: 99%
“…Dispersal decisions are context-dependent (plastic), meaning that organisms adjust them based on information about the surrounding biotic (e.g., predation, kin competition, and intra- and interspecific-competition) and abiotic (e.g., resource availability, spatiotemporal environmental variation) conditions [15]. For instance, organisms are more propense to leave their natal patches when local performance (i.e., fitness) is reduced via strong competition (intraspecific or interspecific), predation, resource scarcity, or unsuitable abiotic conditions [7,16]. These context-dependent decisions underly changes in species’ dispersal strategies to maximize regional fitness and/or minimize local mortality across different ecological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, context-dependent variation in dispersal strategies are species-specific [6,8,16]. Thus, even species that are evolutionary closely related may still exhibit contrasting changes in dispersal strategies when subjected to varying abiotic and biotic conditions [8,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation